Counseling Assistance for Orphans in Krecek Gardens - Diah Retno Ningsih; Khoirul Anwar (Indonesian Journal of Society Development, 2024)
The assistance is carried out at Krecek Nongkojajar Gardens, which is one of the institutions in Kayu Kebek village which aims to build better personality and independence for orphans. Due to the condition of children who do not have complete parents, orphans become targets for assistance. The number of orphans on the Orphan Camp Team list is 45 children with results after the assessment that there are 20 children who need counseling. Mentoring activities are carried out for approximately five months with follow-up activities outside of the scheduled mentoring. From this mentoring activity, changes occur in accordance with the targets to be achieved, including: 1) Individuals have good personality and independence. 2) Individuals gain insight into problem solving